Discrepancies between patient-reported outcomes, and endoscopic and histological appearance in UC - Colombel, Jean-Frédéric (Gut, 2017)
OBJECTIVE: Both endoscopy and histology may be included in the definition of mucosal healing in UC. This study aimed to establish the association between patient-reported outcomes, specifically symptom measures, and the presence of inflammation as measured by endoscopy and histology in UC. DESIGN: Using patient data from an observational multicentre study of UC (n=103), rectal bleeding (RB) and stool frequency (SF) symptom subscores of the Mayo Clinic Score (MCS) were compared with the endoscopic subscore (MCSe) and histology. Faecal calprotectin and biopsy cytokine expression were also evaluated. RESULTS: When identifying UC patients with inactive disease, RB scores were superior to SF scores and the combination (sensitivity/specificity: MCSe=0/1, RB 77%/81%, SF 62%/95%, RB+SF 54%/95%; MCSe=0, RB 87%/66%, SF 76%/83%, RB+SF 68%/86%). Across different definitions of mucosal healing (MCSe≤1; 0; or 0 plus inactive histology), a larger subset of patients reported increased SF (39%, 25% and 27%, respectively) compared with RB (24%, 13% and 10%). Faecal calprotectin and inflammatory cytokine expression were higher in patients with active disease compared with patients with mucosal healing, but there were no differences between patients using increasingly stringent definitions of mucosal healing. CONCLUSIONS: Endoscopically inactive disease is associated with absence of RB but not with complete normalisation of SF. Achieving histological remission did not improve symptomatic relief. In addition, in these patients, higher inflammatory biomarker levels were not observed. These data suggest that non-inflammatory changes, such as bowel damage, may contribute to SF in UC.